Application of the Walktest Method for Optimizing Access Point Coverage in the Main Building of PT PLN (Persero) UIP SUMBAGSEL - Kms. M. Okta Agung Saputra (Institute of Information Technology and Social Science (IITSS), 2024)
This study addresses Wi-Fi network issues in the Main Building of PT PLN (Persero) UIP SUMBAGSEL, which frequently experiences interference, weak signal strength, and blind spots at several points on the third floor. The proposed solution involves applying the walktest method, using the G-Net WiFi tool for data collection, and optimizing access point placement. The study aims to identify areas with weak signal coverage and determine optimal access point locations to improve Wi-Fi network quality. The method includes measuring signal strength at various locations inside the building by walking continuously along specified routes. The results demonstrate that the walktest method is effective for identifying problematic areas and supporting better access point placement. The optimized configuration eliminates blind spots and produces a more stable and evenly distributed Wi-Fi network throughout the third floor.